THE EFFECT OF MAIZE GRAIN TYPE ON DIGESTIBILITY OF STARCH IN THE RUMEN OF SHEEP - Jože VERBIČ; Drago BABNIK; Vida ŽNIDARŠIČ-PONGRAC (Acta Agriculturae Slovenica)
Ruminal starch digestibility of dried maize grain and whole plant maize silage was determined by the in sacco method. It was found out that starch of dent type maize hybrid is more extensively digested in the rumen than starch of flint type hybrid. Digestibilities of dried maize grain from dent and flint type hybrids were 683 and 554 g kg-1 respectively. Ruminal digestibilities of corresponding silages were 915 and 743 g kg-1. Ruminal digestibility of starch in whole plant maize silage was on average about 200 g kg-1 higher than in dried grain samples. Ruminal starch digestibility of maize silages can not be estimated directly on the basis of measurements done on dried grain samples. Some practical implications of differences among hybrids and between dried and ensiled maize are discussed.